Vector population manipulation for control of arboviruses – a novel prospect for India. Issue 4 (19th November 2013) - Niranjan Reddy, BP; Gupta, Bhavna; Rao, B Prasad
Abstract India, the seventh largest country in the world, has diverse geographical and climatic regions with vast rural and peri‐urban areas. Many are experiencing an escalation in the spread and intensity of numerous human diseases transmitted by insects. Classically, the management of these vector‐borne diseases is underpinned by either chemical insecticides and/or environmental management targeted at the vector. However, these methods or their present implementation do not offer acceptable levels of control, and more effective and sustainable options are now available. Genetic strategies for the prevention of arbovirus transmission are most advanced for dengue and chikungunya, targeting their primary vector, Aedes aegypti. The national burden in terms of morbidity and mortality as a direct consequence of dengue virus in India is considered to be the largest worldwide, over 4 times that of any other country. Presently, new genetic technologies are undergoing field evaluation of their biosafety and efficacy in several countries. This paper discusses the merits of these approaches and argues for fair and transparent appraisal in India as a matter of urgency. Identification of any associated risks and their appropriate mitigation are fundamental to that process. © 2013 Society of Chemical Industry